Women in Micro and Small Business Enterprises and their Financial Cruxes in Ethiopia: A Case Study of Mettu Town - S.N. Singh (Financial Markets, Institutions and Risks)
Ethiopia is fast growing economy among countries in the continent of Africa and the participation of skilled women in the small business enterprises has become interesting for the analysis come across. The role of education of women is the crucial one, especially for third world countries like Ethiopia. Thus, the main purpose of this study is to investigate the participation of skilled women in Micro & Small Enterprises in case of Mettu town. This study has attempted to portray participation of educated women in Micro and Small Enterprises in the study area. To conduct this study, the data has been collected from both primary and secondary sources. The primary sources of data obtained through structured questionnaire, interviews and observations however the secondary sources of data are books, journals and different written documents of government as well as NGOs. Descriptive method of statistics has been used to analyze the data. The findings of the study reveal that despite of financial crunches the participation of women particularly skilled in MSEs gradually increasing over the period of time in town. Educated women are more likely preferring service sector followed by trade sector in the study area.